Spectral selective fluorescence molecular imaging with volume holographic imaging system - Yanlu Lv; Jiulou Zhang; Fei Liu; Junwei Shi; Huizhi Guang; Jing Bai; Jianwen Luo (Journal of Innovative Optical Health Sciences, 2016)
A compact volume holographic imaging (VHI) method that can detect fluorescence objects located in diffusive medium in spectral selective imaging manner is presented. The enlargement of lateral field of view of the VHI system is realized by using broadband illumination and demagnification optics. Each target spectrum of fluorescence emitting from a diffusive medium is probed by tuning the inclination angle of the transmission volume holographic grating (VHG). With the use of the single transmission VHG, fluorescence images with different spectrum are obtained sequentially and precise three-dimensional (3D) information of deep fluorescent objects located in a diffusive medium can be reconstructed from these images. The results of phantom experiments demonstrate that two fluorescent objects with a sub-millimeter distance can be resolved by spectral selective imaging.